The impact of electronic medical records on nurse productivity and nursing job enrichment: An empirical study within a South African hospital - Kangethe, Matheri (My University, 2014)
Electronic Medical Record (EMR) Systems hold considerable potential for improving the cost and quality of health care delivery. Yet, little is known about nurses’ perceptions of EMR systems and the impacts of EMR system implementations on nursing outcomes in particular, nurse productivity and the nursing job enrichment. This research study therefore examines nurses’ satisfaction with EMR use and assesses the impacts of use on individual nurse productivity and how the nurse’s role is enriched by this technology. DeLone and McLean (1992) IS Success Model and Bhattacherjee’s (2001) Post Acceptance Model form the basis for this assessment.